The Application Of Interpersonal Communication In Overcoming Conflicts Between Adolescents In Palakka Sub-District, Bone District - Nurmalia; Muliaty Amin; Firdaus Muhammad (TASAMUH, 2024)
This article discusses the application of interpersonal communication in overcoming conflicts between adolescents in Palakka District, Bone Regency. The main problem in this study is how the application of interpersonal communication in overcoming conflicts among adolescents in Palakka District, Bone Regency. From the main problem, the researcher put forward sub-problems, namely, How is the process of applying interpersonal communication in overcoming conflicts between adolescents in Palakka District, Bone Regency? and How is the effectiveness of the application of interpersonal communication in overcoming conflicts between adolescents in Palakka District, Bone Regency? This research uses qualitative methods that collect data through observation, interviews, and documentation. The results showed that the application of interpersonal communication in overcoming conflicts between adolescents in Palakka District, Bone Regency, was carried out through counseling with the theme of communication, approaches through parents, government, and teachers to adolescents, dyadic communication, and small group communication. Then, the effectiveness of the application of interpersonal communication in overcoming conflicts between adolescents in Palakka District, Bone Regency, namely, adolescents always apply an open attitude so that they can tell the conflicts experienced, empathy helps adolescents in constructively handling conflicts, support from parents and other people can affect a child's identity which can increase his ability to adapt to a problem, adolescents do positive activities to overcome the conflicts that occur. Moreover, various efforts ensure that equality is always applied wherever it is